2022
DOI: 10.1002/adfm.202201069
|View full text |Cite
|
Sign up to set email alerts
|

Biointerface Engineering with Nucleic Acid Materials for Biosensing Applications

Abstract: Molecular recognition at the biointerface plays a critical role in sensing molecular interactions (e.g., DNA hybridization) and extracellular changes, which can directly affect the detection performance of biosensors (e.g., sensitivity, specificity, and response dynamics). However, conventional sensing biointerfaces show low molecular recognition efficiency due to limited target accessibility. Engineering sensing biointerfaces to regulate the orientation, spacing, and density of surface‐confined molecular prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 554 publications
(349 reference statements)
0
18
0
2
Order By: Relevance
“…Recent researches have reported that some DNA scaffold-based structures can colocalize successive DNA reactants in a confined space to keep the reaction reagents in relatively high concentrations, facilitating the substrate transport and subsequently the HCR rate. For instance, Reif et al designed a DNA origami rectangle to orderly localize DNA hairpins on its surface, thus significantly speeding up the kinetics of DNA hybridization . Similarly, Merkx et al fabricated a DNA-functionalized supramolecular polymer and used it as an efficient platform for molecular computing; thus, the kinetics of strand displacement and strand exchange reactions are greatly accelerated by 2 orders of magnitude .…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches have reported that some DNA scaffold-based structures can colocalize successive DNA reactants in a confined space to keep the reaction reagents in relatively high concentrations, facilitating the substrate transport and subsequently the HCR rate. For instance, Reif et al designed a DNA origami rectangle to orderly localize DNA hairpins on its surface, thus significantly speeding up the kinetics of DNA hybridization . Similarly, Merkx et al fabricated a DNA-functionalized supramolecular polymer and used it as an efficient platform for molecular computing; thus, the kinetics of strand displacement and strand exchange reactions are greatly accelerated by 2 orders of magnitude .…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the ladder-shaped drug carriers are rigid enough to load a 66 kDa tetrameric protein, i.e., streptavidin (STV), in every drug loading site. We believe that our drug carriers have the ability to carry many kinds of drugs that can meet the requirements for diagnosis and therapy, and can serve as important tools for the study of biosensors [ 42 ], structural scaffolds [ 43 ], molecule machines [ 44 ], and more.…”
Section: Introductionmentioning
confidence: 99%
“…The development of functional DNA-based cell surface sensors has opened new possibilities for in situ imaging of cancer biomarkers in the TME. 8–13 Benefiting from the exceptional programmability and flexibility of functional DNA, these sensors enable the detection of various relevant information in the TME with high spatial resolution, including extracellular pH, 14,15 metal ions, 16 small molecules, 17 and gaseous molecules. 18,19 Despite remarkable progress, current approaches for cell surface localization imaging and biosensing within the TME typically depend on lipid-based membrane modification or chemical modification for cell surface engineering.…”
Section: Introductionmentioning
confidence: 99%